Proton therapy for adult craniopharyngioma: Experience of a single institution in 91 consecutive patients. Issue 4 (25th August 2022) - Beddok, Arnaud; Scher, Nathaniel; Alapetite, Claire; Baussart, Bertrand; Bentahila, Ghita; Bielle, Franck; Bolle, Stephanie; Dendale, Remi; Dureau, Sylvain; Goudjl, Farid; Helfre, Sylvie; Mammar, Hamid; et al.
Abstract: Background: Craniopharyngioma (CP) in adults is a rare benign tumor associated with many morbidities, with limited contemporary studies to define treatment, and follow-up guidelines. Methods: A single-center retrospective study was conducted on patients aged ≥ 18 years from 2006–2018 with CP and who were treated with proton therapy (PT). Late toxicity was defined as a minimum of 18 months from diagnosis. Overall survival (OS), local recurrence-free survival (LRFS), and toxicity were characterized using Kaplan–Meier and Cox regression analyses. Results: Ninety-one patients met the criteria, with a median age of 37 years (range 18–82 years). PT was conducted after tumor resection in 88 patients (97%), in 64 patients (70.3%) as an adjuvant strategy and in 27 (29.7%) after recurrent disease. Three patients received exclusive PT. A median MRI follow-up of 39 months revealed 35.2% complete response, 49.5% partial response, and 9.9% stable disease. Five patients developed local recurrence (LR). The pattern of failure study showed that these five LR were within the GTV volume. The 5-year LRFS was 92.0% [CI 95% 84.90–99.60]. All the patients were alive at the end of the follow-up. Patients requiring treatment adaptation during PT tend to have a higher risk of LR ( P = .084). Endocrinopathy was the most frequent grade ≥ 2 late toxicity. Among patients who were symptom-free before the start of treatment, none developed hearing toxicity but four (9.8%) developed visual disorders and 10 (11.3%) symptomatic memory impairment. Patients with large tumors had a higher risk of developing symptomatic memory impairment ( P = .029). Conclusion: Adults with CP treated with PT have favorable survival outcomes, with acceptable late toxicity. Prospective quality-of-life and neurocognitive studies are needed to define late adverse effects better.